Design and Valuation of Debt Contracts - Anderson, Ronald W.; Sundaresan, Suresh (Review of Financial Studies, 1996)
This article studies the design and valuation of debt contracts in a general dynamic setting under uncertainty. We incorporate some insights of the recent corporate finance literature into a valuation framework. The basic framework is an extensive form game determined by the terms of a debt contract and applicable bankruptcy laws. Debtholders and equityholders behave noncooperatively. The firm’s reorganization boundary is determined endogenously. Strategic debt service results in significantly higher default premia at even small liquidation costs. Deviations from absolute priority and forced liquidations occur along the equilibrium path. The design tends to stress higher coupons and sinking funds when firms have a higher cash payout ratio.